Hexavalent chromium removal in contaminated water using reticulated chitosan micro/nanoparticles from seafood processing wastes - Dima, Jimena Bernadette (2015)
Chitosan particles (CH) were obtained from seafood processing wastes (shrimp shells) and physicochemically characterized; deacetylation degree of CH was measured by Infrared Spectroscopy (FTIR) and potentiometric titration; polymer molecular weight was determined by intrinsic viscosity measurements. Reticulated micro/nanoparticles of chitosan (MCH) with an average diameter close to 100. nm were synthesized by ionic gelation of chitosan using tripolyphosphate (TPP), and characterized by SEM, size distribution and Zeta-potential. Detoxification capacities of CH and MCH were tested analyzing the removal of hexavalent chromium Cr(VI) from contaminated water, at different initial chromium concentrations. The effect of pH on adsorption capacity of CH and MCH was experimentally determined and analyzed considering the Cr(VI) stable complexes (anions) formed, the presence of protonated groups in chitosan particles and the addition of the reticulating agent (TPP). Chitosan crosslinking was necessary to adsorb Cr(VI) at pH. <. 2 due to the instability of CH particles in acid media. Langmuir isotherm described better than Freundlich and Temkin equations the equilibrium adsorption data. Pseudo-second order rate provided the best fitting to the kinetic data in comparison to pseudo-first order and Elovich equations. Chemical analysis to determine the oxidation state of the adsorbed Cr, showed that Cr(VI) was adsorbed on CH particles without further reduction; in contrast Cr(VI) removed from the solution was reduced and bound to the MCH as Cr(III). The reduction of toxic Cr(VI) to the less or nontoxic Cr(III) by the reticulated chitosan micro/nanoparticles can be considered a very efficient detoxification technique for the treatment of Cr(VI) contaminated water.